Laser à fibra dopada com érbio em regime de acoplamento híbrido de modos com absorção saturável baseada em nanotubos de carbono - Pertile, Heidi Kaori Sato (2013)
In this work we present a study on the generation of pulse train in an Erbium doped fiber laser in the hybrid mode-locking regime operating with short pulses at high repetition rates. The short pulses are generated by passive mode-locking technique using carbon nanotubes as saturable absorbers. High repetition rates are generated by active mode-locking technique using a phase modulator. We built cavities with three different mode-locking regimes: active, passive and, finally, hybrid, to compare results. In active and hybrid cavities we used an electro-optical modulator. In passive and hybrid cavities we used a homemade film of a polymer containing carbon nanotubes with diameter of 1 nm. With the cavity operating in the hybrid regime we obtained pulse durations of 1.77 ps with repetition rate of 10 GHz.